Goose on the loose - Cox, Phil Roxbee; Cartwright, Stephen; Tyler, Jenny (Tulsa, Okla. : EDC, 2001)
Goose has many adventures while riding her scooter.
"A phonics reader"--Cover.
Lift the flap pages.
3.0.
3.0
K-3
Keywords: Toy and movable books -- Specimens; Geese -- Fiction; Stories in rhyme; Toy and movable books; Geese -- Fiction; Stories in rhyme; Toy and movable books